Circadian variation of ticagrelor-induced platelet inhibition in healthy adulty. Issue 3 (6th February 2018) - Fournier, Stephane; Guenat, Florine; Fournier, Anne; Alberio, Lorenzo; Bonny, Olivier; Bertaggia Calderara, Debora; Bardy, Daniel; Lauriers, Nathalie; Harbaoui, Brahim; Monney, Pierre; Pascale, Patrizio; Eeckhout, Eric; et al.
Abstract: Aims: The circadian variation of platelet aggregation is well demonstrated. However, whether this has an impact on antiplatelet inhibition therapy is poorly documented. We aimed to observe whether ticagrelor-induced platelet inhibition follows a circadian rhythm. Methods and results: The study included 25 healthy volunteers (11 female; 14 male). Blood samples were collected every 4 h. Ticagrelor was added in vitro at a concentration that provided 50% inhibition of the maximum response using the VerifyNow System Platelet Reactivity Test ® thus avoiding any bias induced by circadian gastrointestinal absorption. Platelet aggregation testing was subsequently performed using the VerifyNow. Circadian changes in total platelet count, percentage of platelets inhibition, Von Willebrand activity, and volunteers' physiological parameters were analysed by fitting individuals' data to a sine curve with a 24-h period. Volunteers' physiological parameters [heart rate (b.p.m.), systolic/diastolic blood pressure (mmHg), and body temperature (Celsius)] followed a significant mean circadian pattern of 6 b.p.m. ( P  < 0.001), 5 mmHg/7 mmHg ( P  < 0.002), and 0.3°C ( P  < 0.001), respectively. Ticagrelor-induced platelet inhibition was significantly lower at 13:00 (38.4%) than at any other time (45.2%) ( P  = 0.018). Percentage of inhibited platelets plotted against time followed a circadian rhythm ( P  < 0.001), with mean minimum/maximum values at 13:00/02:00, respectively. Von Willebrand activity also followed a circadian pattern ( P  < 0.001), with an amplitude of 12.24% and a maximum activity at 12:00. Conclusion: Ticagrelor-induced platelet inhibition follows a circadian rhythm, with the lowest mean values achieved at 13:00. These results deserve further studies in patients with coronary artery disease.